PENGARUH GAYA KEPEMIMPINAN, KEDISIPLINAN, DAN KOMPENSASI TERHADAP MOTIVASI KERJA - Ahmad Agus Saikhoni; Sujiono Sujiono; Purwanto Purwanto (Universitas Muhammadiyah Ponorogo, 2020)
Human Recources is one of the factors that determine the success of failure of HR companies company’s overall goals. Humans are a resource factor that is different from other factors, because humans have feelings, HR must be managed and fostered carefully and thoroughly in order to be able to make optimal contributions to the company. This study refers to the understanding of leadership style, discipline and compensation for the work motivation of employees of PT. UNIRAMA DUTA NIAGA is in ponorogo. This research is a quantitative descriptive study, while the research instrument is a questionnaire. The population used in this study were employees of PT. UNIRAMA DUTA NIAGA. Employees in this company approve 61 employees. Testing data instrument used were validation and reliability tests. Testing analysis and coefficient of determination, while testing the hypothesis using the t test and f test. The result of this study are (1) leadership style has an influence on employee work motivation with regression regression of 0.241 at the significance of 0.008. (2) Dicipline affects significant work motivation with a regression value of 0.119 with a significancevalue of 0.36. (3) Compencation is also significant on employee work motivation with a total regression of 0.519 with a significance value of 0,000. (4) leadership style, discipline, and compensation simultaneously have a significant influence on work motivation with a significance level value, 0117.